2021
DOI: 10.3390/ma14216674
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life of Austenitic Steel 304 Bolts Strengthened by Surface Treatment with Graphene Oxide Layer and Surface Shot Peening

Abstract: This paper presents the results of investigations of the effect of graphene oxide and surface shot peening on the mechanical properties and fatigue life of bolts made of austenitic 304 steel. An innovative method for the uniform deposition of graphene oxide on screws is presented. The process involved activating the surface using plasma and then performing graphene oxide deposition using centrifugal force and vacuum drying. The screw specimens prepared in this way were subjected to a surface peening process. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…After analyzing the test results, it should be noted that the graphene oxide coating alone deposited on the steel did not unequivocally increase its fatigue life. Therefore, it is proposed that an additional strengthening treatment be carried out such as mechanical shot peening, which allows the deposited graphene oxide coating to be introduced into the surface layer and takes advantage of the unique properties of graphene to unequivocally increase durability, as the authors presented in [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After analyzing the test results, it should be noted that the graphene oxide coating alone deposited on the steel did not unequivocally increase its fatigue life. Therefore, it is proposed that an additional strengthening treatment be carried out such as mechanical shot peening, which allows the deposited graphene oxide coating to be introduced into the surface layer and takes advantage of the unique properties of graphene to unequivocally increase durability, as the authors presented in [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in many research centers, there are attempts to deposit graphene and its derivatives on the surface of construction materials using other methods, such as those with the use of an aerosol [ 11 ]. Studies performed on 304 steel bolts showed that hybrid graphenation (shot peening of a graphene layer deposited on the steel surface) leads to an increase in fatigue life of 42–275% (depending on the stress amplitude level) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…at the Biomedical Engineering Center of the Institute of Optoelectronics of the Military University of Technology, according to the methodology developed, which included plasma purification followed by the deposition of graphene oxide using centrifugal forces (centrifugal method) and vacuum drying of screws with an embedded graphene layer (patent application). The process of graphene oxide deposition on the screw surfaces is described in [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The processing of elements presented in this work consisted of plasma cleaning and surface activation, the application of graphene oxide, vacuum drying, and mechanical shot peening. This is known as hybrid graphene treatment and is presented in patent application P. 438715 [ 14 ].…”
Section: Patentsmentioning
confidence: 99%